BUILDING CHARACTER OF ALTRUISM PRAXIS IN ENGLISH TEACHING AND LEARNING AT MAN KARAWANG - Ibrahim, Fina Aufar Laela (IJLECR (International Journal of Language Education and Cultural Review), 2020)
This study aimed at investigating the altruism praxis in English teaching and learning classroom activities in Senior High School. This study employed a case study and conducted in MAN Karawang. The data in this study were the occurence of altruism aspects in English teaching and learning classroom activities. This study employed two instruments in collecting data, namely observation and interview. This study revealed that three aspects of altruism, empathy; prosocial behavior and aversive-arousal reduction appeared in English teaching and learning classroom activities and the most dominant is prosocial behavior. In other words, it can be concluded that MAN Karawang has contributed in altruism praxis in English teaching and learning classroom activities. The contribution is shown by habituating and maintaining the behaviors that represent aspects of altruism, such as Student follows teacher`s instruction; Student lends others stuffs they do not have and student uses positive language during discussion.